Total phenols, ascorbic acid, b-carotene and lycopene in Portuguese wild edible mushrooms and their antioxidant activities - Barros, Lillian (2008)
The antioxidant activities of three Portuguese wild edible mushroom species, Leucopaxillus giganteus, Sarcodon imbricatus, andAgaricus arvensis, were evaluated. Methanolic extracts were screened for their reducing power, 2,2-diphenyl-1-picrylhydrazyl (DPPH) radicalscavenging capacity, inhibition of erythrocytes hemolysis and antioxidant activity using the b-carotene linoleate model system. The amounts of ascorbic acid, b-carotene and lycopene found in the mushroom extracts were very low. Otherwise, the high contents of phenolic compounds might account for the good antioxidant properties found in all species. L. giganteus had the highest content of phenols and proved to be the most active, presenting lower EC50 values in all the antioxidant activity assays.